Nurse Participation in Colonoscopy Observation versus the Colonoscopist Alone for Polyp and Adenoma Detection: A Meta-Analysis of Randomized, Controlled Trials - Lei Xu; Yu Zhang; Haojun Song; Weihong Wang; Sijie Zhang; Xiaoyun Ding (Gastroenterology Research and Practice)
The role of nurse participation (NP) in colonoscopy observation for polyp and adenoma detection is unclear. This study aimed to evaluate whether nurse participation can improve polyp and adenoma detection. Patients and Methods. The PUBMED, EMBASE, and Cochrane Library databases were searched for randomized controlled trials (RCTs) published in English. The outcome measurements included (1) the polyp and adenoma detection rate (PDR and ADR); (2) the advanced lesions detection rate; and (3) the mean polyp and adenoma detection rate per colonoscopy. Results. Three RCTs with a total of 1676 patients were included. The pooled data showed a significantly higher ADR in the NP group than colonoscopist alone (CA) (45.7% versus 39.3%; RR 1.16; 95% CI, 1.04–1.30). And it showed no significant difference in the PDR and advanced lesions detection rate between the two groups (RR: 1.14, 95% CI: 0.95–1.37; RR: 1.35, 95% CI: 0.91–2.00; resp.). Conclusions. Nurse participation during a colonoscopy can improve the ADR, whereas no benefit for the PDR and advanced lesions detection rate was observed. All RCTs included in the meta-analysis had high risk of bias. Thus, there is a need for new research that uses sound methodology to definitively address the research question under study.